Christian Gregor’s “Treatise Concerning the Singing in the Brethren Congregation” (1784): A Bilingual Edition - Vogt, Peter (Journal of Moravian history, 2021)
In 1784 Christian Gregor wrote a treatise on the Moravian understanding and practice of singing, intended as a contribution for the Deutsche Encyclopaedie, a multivolume dictionary project of the German Enlightenment. It appeared in print in 1787, yet it was also circulated in the 1784 edition of the “Gemeinnachrichten,” to be read for instruction and edification in Moravian congregations and societies. Moreover, an English translation appeared in the 1784 edition of the “Congregational Accounts,” the British counterpart of the “Gemeinnachrichten.” Gregor’s essay offers a detailed account of spiritual and practical aspects of Moravian singing. Because this important text is not widely known, it is offered here in the form of an annotated bilingual edition.